The impact of two-way FDI on the upgrading of China’s industrial structure: Based on the research in Chongqing - Wei, Zhiqi; Li, Mingxuan; Li, Yitong; You, You (Journal of Asian Business Strategy, 2024)
The improvement in the economic environment and the implementation of the “bring in and go global” strategy have had an impact on China's economic development and the optimization of its economic structure. The decline of Chongqing's traditional pillar industries has made the promotion of economic structure upgrading a key to economic development. The purpose of this paper is to study the role of two-way foreign direct investment (FDI) in industrial structure upgrading. This paper is designed to study the effect of outward foreign direct investment (OFDI) and inward foreign direct investment (IFDI) on the industrial structure upgrading from both theoretical and empirical perspectives. This study selects data from Chongqing from 1987 to 2022 and uses Stata 17.0 software for empirical analysis, based on Chenery’s “standard structure” industrial change model. The research findings show that OFDI and IFDI have a significant positive impact on the intensification and servicification of Chongqing's industrial structure and are significant at the 0.01 level. OFDI and IFDI have a significant positive impact on the rationalization of Chongqing's industrial structure and are significant at the 0.05 level. This means that two-way FDI has a positive effect on the optimization of industrial structure. The practical implication of this study is that it provides a realistic basis for Chongqing to fully leverage the advantages of international direct investment and promote the optimization and upgrading of the industrial structure, which also has enlightening significance for China’s economic structure reform.